An experimental investigation of flow boiling instability in a natural circulation loop. (February 2018) - Chen, Xianbing; Gao, Puzhen; Tan, Sichao; Yu, Zhiting; Chen, Chong
Highlights: Flow boiling instabilities with flow reversal are found in a macro-channel. The long period and large amplitude flow instabilities are classified as PDOs. Flow reversal is caused by the onset of CHF and accompanied by periodic dryout. A comparison is made between flow reversal in macro-channel and micro/mini-channel. Abstract: An experimental investigation of flow boiling instability in a single macro-channel natural circulation loop at high inlet subcooling and low pressure is performed. Flow boiling instabilities without and with flow reversal which are classified as pressure drop oscillations are observed. The characteristics of flow reversal in a single macro-channel are illustrated. Flow reversal is verified on the basis of three evidences: negative inlet flowrate, inlet water temperature pulse and large amplitude pressure oscillations in the compressible volume. The mechanism of flow reversal is given by correlating experimental heat fluxes with CHFs predicted by Umekawa correlation and Zhao correlation. It can be concluded that flow instability induces the premature of CHF. Flow reversal is caused by the onset of CHF and accompanied by periodic dryout and rewetting. Flow regime in the heated channel is depicted based on the exit water temperature oscillations, heating surface temperature profile and periodic dryout. A comparison has been made for the mechanism of flow reversal between macro-channel and micro/mini-channel. Three prerequisites contribute to the occurrence of flow reversal in a macro-channel: (1) low pressure natural circulation, (2) long two-phase region and (3) upstream compressible volume. Lastly, a stability map which distinguishes the boundaries of flow instabilities without and with flow reversal is given.